O-rgyan Gu-ruʼi sbas gnas: gnas chen rong rtse = A guide to sacred site of Guru Rinpoche : Rongtse Ney - Rin-chen-mkhaʼ-ʼgro (Richen Khandu, 2021)
A guide book to sacred site of Guru Rinpoche-Rongtse Ney in Bhutan